The Bent-Tube Nozzle Optimization of Force-Spinning With the Gray Wolf Algorithm - Liu, Kang; Li, Wenhui; Ye, Peiyan; Zhang, Zhiming; Ji, Qiaoling; Wu, Zijun (Frontiers in Bioengineering and Biotechnology, 2021)
Force-spinning is a popular way to fabricate various fine fibers such as polymer and metal nanofibers which are being widely employed in medical and industry manufacture. The spinneret is the key of the device for spinning fibers and the physical performance and morphology of the spun nanofibers are largely determined by its structure parameters. In this paper, the effect of spinneret parameters on the outlet velocity is explored and the spinneret parameters are also optimized to obtain the maximum outlet velocity. The mathematical model of the solution flow in four areas is established at first and the relationship between outlet velocity and structure parameters is acquired. Then the optimal parameters of outlet diameter, bending angle and curvature radius are obtained combining with the Grey wolf algorithm (GWA). It is found that curved-tube nozzle with bending angle of 9.1 °, nozzle diameters of 0.6mm and curvature radius of 10mm, can obtain the maximum outlet velocity and better velocity distribution. Finally, the fiber of 5wt% PEO solution is manufactured by straight-tube nozzle and optimized bent-tube nozzle in the laboratory and the morphology as well as diameter distribution was observed by Scanning Electron Microscope (SEM). The results showed that the outlet velocity is improved dramatically after the bend-tube parameters optimized by GWA and the nanofibers of better surface quality could be obtained by optimized bend-tube.